ANALYSIS OF THE EFFECTIVENESS OF THE RICE SEED INDEPENDENCE PROGRAM ON FARMER CAPACITY AND INCOME IN PASAR MIRING VILLAGE, PAGAR MERBAU DISTRICT, DELISERDANG REGENCY - Adriansyah Yoesoef; Syarifah Mayly; Irshad Ahmad Reshi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to analyze farmer characteristics, the effectiveness of the Thousand Independent Seed Villages (SDMB) Program, and the income of seed farmers in Pasar Miring Village, Pagar Merbau District, Deliserdang Regency. The research method used a census approach with 25 farmers as respondents. Data were collected through interviews, observations, and literature studies, then analyzed descriptively and quantitatively. The results showed that most farmers were of productive age, experienced, but had low levels of education. The SDMB program was classified as effective based on aspects of understanding, targeting accuracy, and program planning. However, from an economic perspective, the seed nursery business has not been profitable because the R/C ratio is less than one and the net income is negative. This indicates that the business is still a side business. Therefore, technological improvements, seed certification, and strengthening marketing are needed to increase farmer income.